The knowledge of South African venous thromboembolism: prophylactic and therapeutic practice guidelines of registrars in anaesthesiology and orthopaedic surgery at the University of the Witwatersrand - Dadabhay, Zeenat (My University, 2018)
thromboembolism:  Prophylactic  and   therapeutic  practice  guideline  has  been  developed  to  aid  clinicians  with  the   correct  administration  of  thromboprophylaxis.  This  can  reduce  the  incidence  of   venous  thromboembolism  (VTE)  and  thus  the  associated  morbidity,  mortality   and  socio  economic  implications.  However,  studies  have  shown  that  without   other  interventions,  adherence  to  clinical  guidelines  is  poor.       Method:  A  prospective,  contextual,  descriptive  study  was  undertaken  to   determine  the  knowledge  of  registrars  in  anaesthesiology  and  orthopaedic   surgery  of  the  Venous  thromboembolism:  Prophylactic  and  therapeutic  practice   guideline  (2013).  A  self-‐-‐-‐administered  questionnaire  was  developed  in   consultation  with  experts.  Convenience  sampling  was  used  and  all  registrars   present  at  departmental  academic  meetings  were  invited  to  participate.       Results:  Of  the  participants  only  12  (12%)  obtained  the  specified  pass  mark  of   greater  than  or  equal  to  80%.  Of  the  participants  10  (14%)  of  the  anaesthetic   registrars  and  2  (7%)  of  the  orthopaedic  registrars  achieved  the  required  pass   mark.  Anaesthetic  registrars  achieved  a  mean  score  of  56%  .  Orthopaedic   registrars  achieved  a  mean  score  of  44%.  Two  junior  registrars  (4%)  and  10   senior  registrars  (18%)  achieved  the  required  pass  mark.  Senior  registrars   scored  significantly  (p=0.002)  higher  than  their  junior  colleagues  (56%  vs  48%)       Conclusion:  Knowledge  of  The  Guideline  amongst  registrars  was  poor  and  room   for  improvement  and  intervention  in  order  t
Witwatersrand,  Johannesburg,  in  partial  fulfillment  of  the  requirements  for  the   degree  of  Master  of  Medicine  in  the  branch  of  Anaesthesiology   Johannesburg,  2018
Keywords: Prophylactic and Therapeutic Practice; Venous Thromboembolism; Medical Staff, Hospital (Registrars)